Educação a distância e material didático: um estudo sobre o curso mídias na educação - Bento, Maria Dalvaci (2013)
The thesis Distance learning and didactic material: a study about the course Media in the education in Natal shows a research about the didactic material and its insertion in the distance training course to teachers. In this sense, this research aims to contribute to some universities with reflections about the way to elaborate the didactic material to the distance training course of teachers with the following specific objectives: a) identify some aspects in the didactic material in the extension course Media in the Education that difficult media usage by the teachers members of the course in the pedagogical practice; b) discuss about the way how didactic material to the distance training course to teachers has been created; c) stimulate teachers/members to integrate media in their teacher practice. For that reason, we have developed an action-research (THIOLLENT, 2011; FRANCO, 2005), based on it we elaborated a proposal do complement activities to the course Media in the Education that were applied to two classes during the fifth edition of this course. This research is presented in four steps: 1st) analyze of the course modules; 2nd) creation of a proposal to complement the activities; 3rd) applying the proposal to the students during the fifth edition to the course; 4th) analyze of forums and log books written by teachers/students. Data was analyzed by the contents perspective of Bardin (2011). As a theoretical support, we have Tardif (2012), about teachers knowledge; Dewey (1959; 2011) and Freire (2001; 2009; 2010a; 2010b; 2012) related to learning perspective; Candau (2002), Rays (2003) and Freire (2010a), about the relation theory x practice in the teacher training; Andrade (2003; 2009) and Belloni (2010) about distance teacher training; Bérvot; Belloni (2009), Neves; Medeiros (2005) and Prado (2005), related to Media integration. This research revealed the didactic material of the course Media in the Education has not a proposal to articulate theory and practice, due to this, this course opposed the Media integration. For that reason, teachers/members have real problems to integrate Media in their scholar routine. This research confirmed the way this didactic material was formulated did not help the teachers/students to integrate media in their pedagogical activities